Land Use Change Prediction Modelling in Nam Ha National Protected Area, Luangnamtha Province in 2025 - Phengvichith, Vansaleum (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This study investigates land use change trends within Nam Ha national protected area (NPA), Luang Namtha Province, objective of the research in this chapter is to predict land use change trends for the year 2025 using the CA-MARKOV model. Historical land use data were derived from Landsat 5 and Landsat 8 satellite imagery captured in 2005, 2010, and 2015. These datasets were systematically analyzed and classified to identify distinct land use categories, which were subsequently integrated into the CA-MARKOV model for predictive analysis. The findings reveal a projected reduction in forest area by 2,334 hectares and a decrease in shrubland area by 194 hectares. Conversely, non-forest area are anticipated to expand by 2,273 hectares, while plantations area are expected to increase by 254 hectares. These transitions exhibit complex and varied dynamics of land use gains and losses, underscoring the heterogeneous nature of landscape change in the region. The outcomes of this study provide critical insights for policymakers, land managers, and other stakeholders, offering a scientific basis for informed decision-making. These projections can guide land use planning, educational initiatives, and policy development aimed at safeguarding forest ecosystems and ensuring their sustainable management in alignment with broader developmental and environmental strategies.